Case Report: Uterine Anomalies in Girls With a Congenital Solitary Functioning Kidney - van Dam, Mark J. C. M.; Zegers, Bas S. H. J.; Schreuder, Michiel F. (Frontiers in Pediatrics, 2021)
Unilateral renal agenesis and multicystic dysplastic kidney, resulting in a contralateral solitary functioning kidney (SFK), are part of the broad spectrum of congenital anomalies of the kidney and urinary tract (CAKUT). In girls with SFK, screening for asymptomatic Müllerian anomalies of uterus and vagina is not yet routinely performed, and therefore often overlooked until clinical complications in the menstrual cycle or fertility process occur. In this case series, we report on four teenagers with congenital SFK presenting with menstrual problems due to a Müllerian anomaly. Routine peri-menarchal screening for Müllerian anomalies in girls with SFK may provide timely counseling, surgical treatment and prevention of associated complications such as endometriosis, infertility and miscarriages.